Effect of superficial cervical plexus block on baroreceptor sensitivity in patients undergoing carotid endarterectomy - Demirel, Serdar; Celi de la Torre, Juan Antonio; Bruijnen, Hans; Martin, Eike; Popp, Erik; Böckler, Dittmar; Attigah, Nicolas (Journal of cardiothoracic and vascular anesthesia, 2016)
Objectives - Regional anesthesia for patients undergoing carotid endarterectomy is associated with improved intraoperative hemodynamic stability compared with general anesthesia. The authors hypothesized that the reported advantages might be related to attenuated ipsilateral baroreflex control of blood pressure, caused by chemical denervation of the carotid bulb baroreceptor nerve fibers. - Design - A prospective cohort study. - Setting - Single-center university hospital. - Participants - The study included 46 patients undergoing carotid endarterectomy using superficial cervical block. - Interventions - A noninvasive computational periprocedural measurement of baroreceptor sensitivity was performed in all patients. Two groups were formed, depending on the patients’ subjective response to surgical stimulation regarding the necessity of additional intraoperative local anesthesia (LA) administration on the carotid bulb. Group A (block alone) included 23 patients who required no additional anesthesia, and group B (block + LA) consisted of 23 patients who required additional anesthesia. - Measurements and Main Results - Baroreceptor sensitivity showed no significant change after application of the block in both groups (group A: median [IQR], 5.19 [3.07-8.54] v 4.96 [3.1-9.07]; p = 0.20) (group B: median [IQR], 4.47 [3.36-8.09] v 4.53 [3.29-8.01]; p = 0.55). There was a significant decrease in baroreceptor sensitivity in group B after intraoperative LA administration (median [IQR], 4.53 [3.29-8.01] v 3.31 [2.26-7.31]; p = 0.04). - Conclusions - Standard superficial cervical plexus block did not impair local baroreceptor function, and, therefore, it was not related to improved cerebral perfusion in awake patients undergoing carotid endarterectomy. However, direct infiltration of the carotid bulb was associated with the expected attenuation of baroreflex sensitivity.